Novel Variation in Acyl-CoA Synthetase Long Chain Family Member 6 (ACSL6) Results in Protein Structural Modification and Multiple Non-Related Neoplasia in a 46-Year-Old: Case Report - Castillo, María Isabel; Freire, Erick; Romero, Vanessa I.; Arias-Almeida, Benjamín; Reyes, Carlos; Hosomichi, Kazuyoshi (Frontiers in Oncology, 2022)
Multiple non-related neoplasia does not have an established approach and benefit of performing whole-exome sequencing (WES) analysis. We report a 46 -year- old woman who developed astrocytoma, thyroid, and breast cancer within 10 years. WES analysis found a novel missense variant in the ACSL6 gene, and the protein modeling showed an altered secondary and tertiary structures which modifies the binding to cofactors and substrates. ACSL6 is involved in lipid metabolism, expressed in brain, thyroid, and breast tissues, and associated with diverse types of cancer. Our study demonstrates the benefit of WES analysis compared to commercial panels in patients with non-related neoplasia.